Metabolômica de leveduras fermentadoras de xilose na identificação de alvos metabólicos para aumento da produção de etanol 2g - Cavalcanti, Christiane Gonçalves Campos (2019)
One of the challenges in the production of second generation (2G) ethanol is in the development of efficient yeasts to convert xylose into ethanol in the process of fermenting sugars. Thus, the comprehensive analysis of xylose fermenting yeast metabolism is essential to facilitate the identification of the limiting factors in the conversion metabolism of this pentose and, thus, help in the construction of more efficient genetically modified strains. The objective of this work was to use an advanced analytical tool, the metabolomics, to quantify the main metabolites related to the xylose to ethanol conversion pathways in four species of yeast xyloses: Scheffersomyces stipitis, Spathaspora passalidarum, Spathaspora arborariae and Candida Tenuis. The yeasts were grown in xylose under two different growth conditions, aerobic and microaerobic. The preparation of the sample for metabolic analysis included the steps of quenching and extraction of the metabolites, for which the protocols of ice cold methanol and boiling ethanol, were used, respectively. The quantification of the metabolites was performed by ultra high-performance liquid chromatography coupled to tandem mass spectrometry (UHPLC-MS/ MS), using ion-pair chromatography and hydrophilic interaction liquid chromatography. The data obtained in the quantification were processed and treated through analysis of variance (ANOVA) using RStudio software. A total of eleven metabolites of the xylose metabolism pathway were quantified and validated through metabolic flow analysis (MFA) with R2>90. These metabolites were used to construct the metabolic flow of the three species of yeasts (Scheffersomyces stipitis, Spathaspora passalidarum and Spathaspora arborariae) analyzed. The comparison of molecular targets in yeast xylose showed that the S. stipitis and S. passalidarum species have the best yields of ethanol when grown with limited oxygen. The metabolomic analysis performed in this study may help in the genetic improvement of these microorganisms and in the production of 2G ethanol.